Answer:
This is your answer ☺️☺️☺️
So you have x, then you square it to get x^2, then you minus 2x, then +3
The inverse is going backwards so you -3 then +2x then square root x
So you get square root x + 2x -3
I'm pretty sure this is right, sorry if I'm wrong.
3(5y-6)-2y=8
15y-18-2y=8
13y-18=8
13y=26
y=2
That is because you have the expression you can substitute it on the system.( hope this helps)
Unfortunately I do not know the rectangle you are speaking of, if you could provide the rectangle I would be happy to help.
Answer:
He will make $165 every year.
3000 + 165(4) = 3660 (this is his total amount)
He will need 4000 - 3660 = $340
<u><em>He will need an Additional $340.</em></u>